NEW VIEWS ON THE PATHOGENETIC MECHANISMS OF CHRONIC GLOMERULONEPHRITIS - Umarova Tamila Abdufattoevna; Kudratova Zebo Erkinovna; Kosimova Sabina; Nafasova Zarina (Web of Journals Publishing, 2024)
Chronic glomerulonephritis (chronic nephritic syndrome) is a group of diseases heterogeneous in origin and pathomorphology, characterized by immunoinflammatory damage of the tubules, tubules and interstitium of both kidneys and progressive course, resulting in the development of nephrosclerosis and chronic renal failure.
Keywords: chronic glomerulnefritis, genetic predisposition, leukotrienes, cytokines, neutrophils.